Investigation of the ındividual characteristics that predict academic resilience - AVCI, SÜLEYMAN (My University, 2022)
The percentage of students with lower academic achievement than their peers due to their socio -economicaldisadvantages is globally accepted as an indicator of inequality. Some students, despite their disadvantages, areas successful as their advantaged peers. The family and individual characteristics and academic experiences ofthese students, who are referred to as academically resilient, provide useful information to the institutions thatwork to increase the academic success levels of other disadvantaged students. Accordingly, this study aims todetermine the individual characteristics of academically resilient students, focusing on the PISA Turkey results.In line with the OECD criteria, an equal number of academically resilient (N=214) and academicallydisadvantaged (N=214) students participated in the study. Students whose economic, social, and cultural indexvalues are amongst the bottom 25% were considered to be disadvantaged, and those who performed at level 3and above in reading proficiency were regarded to be successful. Eighteen individual characteristics measuredwithin the scope of PISA research were included in the study as independent variables. A binary logisticregression analysis was used in the analysis of the data. The regression model created in line with the findingspredicted 67 percent of the variance in academic resilience and made an accurate classification of 85 percent. Inorder of their power, the predictors of academic resilience are grade repetition, use of metacognitive learningstrategies (understanding, summarizing, evaluating credibility), reading for enjoyment, attitude towardsacademic competition, self-efficacy, and the desired occupation
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Social Sciences and Humanities; Education; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities